2008
DOI: 10.1038/jes.2008.27
|View full text |Cite
|
Sign up to set email alerts
|

Recall bias in the assessment of exposure to mobile phones

Abstract: Most studies of mobile phone use are case-control studies that rely on participants' reports of past phone use for their exposure assessment. Differential errors in recalled phone use are a major concern in such studies. INTERPHONE, a multinational case-control study of brain tumour risk and mobile phone use, included validation studies to quantify such errors and evaluate the potential for recall bias. Mobile phone records of 212 cases and 296 controls were collected from network operators in three INTERPHONE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 44 publications
(45 reference statements)
6
90
2
Order By: Relevance
“…This residual variance is likely to reflect substantial error variance in the self-report measures concerning frequencies of talking and texting. Previous studies show that recall accuracy for mobile phone use is only moderate, in both adolescents (Inyang, Benke, Morrissey, McKenzie, & Abramson, 2009) and adults (Timotijevic et al, 2009Vrijheid et al, 2006Vrijheid et al, 2009), with substantial random error and typically about 20% underestimation of call number and 40% overestimation of call duration. Thus, the observed heritabilities and genetic correlations estimated from these self-report data are probably lower than the true values.…”
Section: Discussionmentioning
confidence: 99%
“…This residual variance is likely to reflect substantial error variance in the self-report measures concerning frequencies of talking and texting. Previous studies show that recall accuracy for mobile phone use is only moderate, in both adolescents (Inyang, Benke, Morrissey, McKenzie, & Abramson, 2009) and adults (Timotijevic et al, 2009Vrijheid et al, 2006Vrijheid et al, 2009), with substantial random error and typically about 20% underestimation of call number and 40% overestimation of call duration. Thus, the observed heritabilities and genetic correlations estimated from these self-report data are probably lower than the true values.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of data collection between interviews and questionnaires are far enough apart that Divan et al mothers with delayed development children were unlikely systematically to under-or overestimate using a cell phone during pregnancy compared to mothers of children with no delayed development. In general, research looking at the agreement between self-reported cell phone use and usage measured by billing or subscription records concludes that individuals tend to overestimate call duration and underestimate the number of calls (29,30). As participation in each round of interviews and questionnaires was voluntary for mothers, it is possible that data were collected for mothers and children participating in the DNBC at only some time points such as 6 months and age 7 years and not have information available at 18 months for the infant.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Interphone questionnaire has been validated against both softwaremodified phones [Vrijheid et al, 2006] and network billing records in adults [Vrijheid et al, 2008]. This latter approach cannot be adopted in children who mainly use prepaid mobile phone services.…”
Section: Discussionmentioning
confidence: 99%